Understanding Novelty in Organizations A Research Path Across Agency and Consequences - Frigotto, Maria Laura (Springer International Publishing, 2018)
Providing a first tentative understanding of novelty and a set of implications for organizations to manage it, this book focuses on the potential offered by emergent novelty, namely novelty which is neither designed nor pursued. The author asks how organizations might increase their abilities and strategies to benefit from its early recognition. Such potential is broken down into positive terms and demonstrates how early recognition is beneficial both to organizations which aim to seize emergent innovations as well as those which aim to avoid emergent disasters. Understanding Novelty in Organizations aims to rethink the structure and strategies of organizations to gain a new balance between design and randomness in the generation of novelty. The varied perspectives presented in this work will engage scholars interested in novelty, innovation and creativity, and emergency management.